Pengaruh fasciolosis pada sapi bali berdasarkan pemeriksaan darah, serum glutamic pyruvic transaminase (SGPT), dan alkaline phosphatase (ALP) - Amirullah Amirullah; Dradjat AS; Sriasih M; Maskur Maskur; Depamede SN; Kisworo D; Kurniasih Kurniasih (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2018)
Investation of Fasciola sp. On several species of cattle in Indonesia has occurred since a long time ago. Fasciolosis caused a high economical loss such as decreasing of carcass and organs, sometimes caused death of calves. The objectives of the research were to evaluate the effect of fasciolosis on Serum Glutamic Pyruvic Transaminase (SGPT), and the obstruction of bile duct by Alkaline Phosphatase (ALP) in Bali cattle suffered from fasciolosis. Faeces of Bali cattle raised in endemic areas of fasciolosis were examinated by sedimentation test to identify eggs per gram of faeces (EPG) of Fasciola sp. The blood samples of cattle which positive to fasciolosis were use to study the hematology by autoanalyser, SGPT and ALP. The results of research showed that from 89 cattle, 28 were infected by Fasciola sp. whithin of 7-115 EPG (min-max). From 20 fasciolosis cattle were indicated that MCHC of 90%, RBC of 30%, HB of 20%, and eosinophils of 2 % of cattle were lower than that of normal standard, while lymphocytes of 60%, MCV of 40%, ALP of 10% and SGPT of 5% of cattle were higher than that of normal standard. hematological appearances of cattle suffered from fasciolosis had macrocytichypochromic anemia, eosinopenia, and lymphocytosis. The increase of SGPT may be caused byhepatic cells destruction by young liver flukes, and the increase of ALP was caused by the obstruction of bile duct by mature liver flukes.